If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 7) * 2 + (y + -1) * 2 = 32 Reorder the terms: (7 + x) * 2 + (y + -1) * 2 = 32 Reorder the terms for easier multiplication: 2(7 + x) + (y + -1) * 2 = 32 (7 * 2 + x * 2) + (y + -1) * 2 = 32 (14 + 2x) + (y + -1) * 2 = 32 Reorder the terms: 14 + 2x + (-1 + y) * 2 = 32 Reorder the terms for easier multiplication: 14 + 2x + 2(-1 + y) = 32 14 + 2x + (-1 * 2 + y * 2) = 32 14 + 2x + (-2 + 2y) = 32 Reorder the terms: 14 + -2 + 2x + 2y = 32 Combine like terms: 14 + -2 = 12 12 + 2x + 2y = 32 Solving 12 + 2x + 2y = 32 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + 2x + -12 + 2y = 32 + -12 Reorder the terms: 12 + -12 + 2x + 2y = 32 + -12 Combine like terms: 12 + -12 = 0 0 + 2x + 2y = 32 + -12 2x + 2y = 32 + -12 Combine like terms: 32 + -12 = 20 2x + 2y = 20 Add '-2y' to each side of the equation. 2x + 2y + -2y = 20 + -2y Combine like terms: 2y + -2y = 0 2x + 0 = 20 + -2y 2x = 20 + -2y Divide each side by '2'. x = 10 + -1y Simplifying x = 10 + -1y
| x=52.5(2/5) | | u^2=3u | | k(x)=2x^2+33x-54 | | x=40(2/5) | | 11=11-10b+2b | | s-3=-5 | | 210.00+0.15x=322.50 | | 4-2=10 | | 3x=2+-1y | | 10x+9=27+7x | | f(-1)=5x+5 | | -(a+3)=-2(2x+3)-7 | | 2(t+2)=14 | | 81xsquared+8=0 | | f=-1 | | 41(x-6)+4=6x-8 | | 9x+7(3x-4)=7-5x | | 4x-2(x-3)=-5+4x+1 | | 9v-9=3(v-5) | | 2x^2+x^2=25*25 | | 4-2(x-3)=5+4x+1 | | 4x-15=x+51 | | 0.5x+9= | | 208=-13 | | 12x^3+28x^2+13x-45=0 | | 3x+10=7x-5 | | 25x^4-50x^3+25x^2=0 | | 8y+2=4x | | 3x+20=41 | | X+(-3)+9=-1+14 | | h(t)=-4.9t^2+24t+8 | | 4x^7-32x^5= |